SITOREM-Based Analysis of Reinforcing Factors of Organizational Commitment among Foundation-Based Vocational Teachers in East Jakarta - Griet Helena Laihad; Soewarto Hardhienata (Sean Institute, 2024)
This study aims to formulate effective strategies to increase organizational commitment among foundation-based permanent teachers at Private Vocational Schools specializing in Computer Engineering and Networking (TKJ) in East Jakarta. The research employs a quantitative approach using the SITOREM (Scientific Identification Theory to Conduct Operation Research in Education Management) analysis technique, which systematically and scientifically identifies priority indicators that need to be addressed. The study population consists of 381 teachers, with a sample of 195 permanent foundation-based teachers. The results of the SITOREM analysis reveal five key indicators that require focused attention to enhance organizational commitment: (1) Salary, (2) Recognition and Awards, (3) Management Support, (4) Sense of Obligation or Indebtedness to the Organization, and (5) Perception of Loss When Leaving the Organization. These five indicators form the foundation for developing strategic steps to improve commitment. The novelty of this study lies in its specific focus on permanent foundation teachers at TKJ Private Vocational Schools in East Jakarta, a subject that has received limited scholarly attention—particularly in the context of organizational commitment using the SITOREM approach. The findings imply that enhancing organizational commitment requires efforts to strengthen individual personality traits, implement transformational leadership, foster a positive organizational culture, and improve teacher job satisfaction. The proposed strategies are expected to create a conducive work environment and foster long-term teacher loyalty to the organization.